Persepsi followers pada akun @Nonnindah sebagai brand ambassador nabila skincare - Anggraeni, Medy; Suryo Sarjono, Herning; Sihabuddin, Sihabuddin (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2024)
This research explores followers' perceptions of the Instagram account Nonnindah as the brand ambassador for Nabila Skincare. The aim is to analyze how followers, particularly those aged 20-30, view her role. Using a descriptive qualitative approach, data was gathered through interviews and documentation.The findings reveal two main perceptions among followers. On the positive side, many believe that Nonnindah effectively communicates the benefits of Nabila Skincare products, enhancing her credibility as a brand ambassador. They appreciate her ability to engage with her audience and promote the products successfully.Conversely, there is a negative perception from some followers who feel that Nonnindah’s content lacks authenticity and tends to be monotonous. They express concerns that her promotional efforts come off as overly commercial and insufficiently creative, impacting their overall engagement with the brand.Overall, the study highlights the mixed responses to Nonnindah's effectiveness as a brand ambassador, reflecting the complexities of influencer marketing in the skincare industry.Keywords : Followers perception, Brand Ambassador, Nonnindah, Media Social, and Nabila Skincare